Pengaruh Motivasi dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Anira Kulta; Nuraida Nuraida; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
This study aims to determine the effect of motivation and knowledge of entrepreneurship on interest in entrepreneurship in class 2018 students of the Dakwah Management Study Program partially and simultaneously. The method used in this research is a quantitative method. In this study the data collection techniques used were observation, interviews, questionnaires and documentation. The data used are primary data and secondary data. The data analysis technique used is multiple linear regression analysis by testing the hypothesis t test (partial) and f test (simultaneous). The data were analyzed using the SPSS version 23 application. The results showed that partially, motivation had a positive effect obtaining a tcount of 2.400 > ttable of 2.026 with a significant value of 0.022 <0.05, entrepreneurial knowledge had a positive effect of obtaining a tcount of 3.375 > ttable of 2.026 with a value significant 0.002 <0.05 on student interest in entrepreneurship. Simultaneously it shows that entrepreneurial motivation and knowledge obtain an fcount value of 27.662 > ftable 3.24 with a significant value of 0.000 <0.05, which means that it has a positive and significant effect on the interest in entrepreneurship for class 2018 students of the Da'wah Management Study Program, Faculty of Da'wah and Communication UIN Raden Fatah Palembang.